Ketika Komikus Bertemu Etnobotanis: Cross-Project Pengembangan Komik Etnobiologi - Fadhlan Muchlas Abrori (The Ethnobiological Society of Indonesia, 2021)
One of the weaknesses in introducing ethnobiology in the learning process is the lack of innovative learning media used. Based on this, it is necessary to develop an interesting medium in introducing ethnobiological research in learning. One of the innovative media that can be used is comics. The purpose of this research is to produce ethnobiological comics, especially ethnobotany which have good quality based on the results of expert judgment and field trials. This research is mixed-method research with two stages, namely the implementation of a project-based learning model between students who take local potential-based learning media development courses, and students who take ethnobotany courses. The next stage is the stage of media development, starting from collecting data from students who take ethnobotany courses, then the results of the research are developed into comics by students who take local potentialbased learning media development courses. The results of this study obtained data that the topics chosen by the students are poison plants for the hunting of the Dayak Lundayeh Tribe, medicinal plants of the Tidung Tribe, ethnopteridology of the Madura Tribe, and traditional ceremonial plants of the Tidung Tribe. The results of the comics that were developed based on expert judgment were valid. Meanwhile, the results of the field trial were feasible.